2020
DOI: 10.1111/den.13883
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for endoscopic submucosal dissection and endoscopic mucosal resection for early gastric cancer (second edition)

Abstract: In response to the rapid and wide acceptance and use of endoscopic treatments for early gastric cancer, the Japan Gastroenterological Endoscopy Society, in collaboration with the Japanese Gastric Cancer Association, produced "Guidelines for Endoscopic Submucosal Dissection and Endoscopic Mucosal Resection for Early Gastric Cancer" in 2014, as a set of basic guidelines in accordance with the principles of evidencebased medicine. At the time, a number of statements had to be established by consensus (the lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
267
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 314 publications
(272 citation statements)
references
References 117 publications
2
267
0
3
Order By: Relevance
“…However, with the development of endoscopy, more and more studies believe that ESD is safe and effective for treating undifferentiated histological types (21,22). Therefore, the latest Japanese guidelines suggest that undifferentiated EGC (≤2 cm) formed by ulcers can be treated with ESD (14). However, it should be carefully considered when determining whether or not to perform an endoscopic submucosal dissection on people with undifferentiated EGC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the development of endoscopy, more and more studies believe that ESD is safe and effective for treating undifferentiated histological types (21,22). Therefore, the latest Japanese guidelines suggest that undifferentiated EGC (≤2 cm) formed by ulcers can be treated with ESD (14). However, it should be carefully considered when determining whether or not to perform an endoscopic submucosal dissection on people with undifferentiated EGC.…”
Section: Discussionmentioning
confidence: 99%
“…When eCuraC lesions are differentiated-type lesionsand fulfill other criteria to be classified into either eCuraA or eCuraB but was either not resected en bloc or had positive HM, they are considered eCuraC-1. All other eCuraC lesions are considered eCuraC-2 (14).…”
Section: Valuation Of Efficacy Of Resectionmentioning
confidence: 99%
“…Regarding the treatment policy for colorectal lesions, polyps of sizes ≤20 mm are assessed to determine whether they can be resected at once with a snare, and the treatment method is selected (either endoscopic mucosal resection or endoscopic submucosal dissection). 5 Polyp size is important information for endoscopists; however, it is challenging to estimate it accurately during the procedure. Chaptini et al reported that only 48% of polyp size estimates were within 20% of the correct value according to a web-based video survey conducted with the participation of 873 endoscopists.…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with a lower rate of adverse events, shorter hospital stay, lower cost, and better quality of life [5][6][7] . Thus, ESD is considered a safe and effective alternative to surgical resection and has become a treatment of choice for EGC and premalignant gastric lesions in Asia 8,9 .…”
Section: Introductionmentioning
confidence: 99%